Sex hormones in postmenopausal women receiving low-dose hormone therapy: The effect of BMI - Lambrinoudaki, I.; Armeni, E.; Rizos, D.; Deligeoroglou, E.; Kofinakos, P.; Kaparos, G.; Alexandrou, A; Creatsa, M.; Logothetis, E.; Kouskouni, E. (Obesity, 2011)
The aim of our study was to evaluate the effect of BMI on the change in circulating sex hormone in postmenopausal women during 6 months of oral continuous combined low-dose hormone therapy (HT). Fifty postmenopausal women were allocated to receive daily one tablet containing combination of 17Β-estradiol (1mg)/norethindrone acetate (0.5mg) for 6 months. Serum levels of follicle-stimulating hormone (FSH), estradiol, total testosterone, sex hormone-binding globulin (SHBG), free androgen index (FAI), free estrogen index (FEI), Δ4-androstendione (Δ4A), and dehydroepiandrosterone sulfate were assessed at baseline and at the end of 6 months. Mean absolute values and percent changes from baseline were compared between lean and overweight women. Mean FSH decreased and mean 17Β-estradiol increased significantly in both groups (FSH lean: 82.3 26.7 decreased to 45.0±17.0mIU/ml, P = 0.0001; FSH overweight: 85.5±22.1 decreased to 52.3±23.8mIU/ml, P = 0.003; P between groups = 0.661; E2 lean: 23.24±12.55 increased to 53.62±28.29pg/ml, P = 0.006; E2 overweight: 24.17±10.88 increased to 68.36± 53.99pg/ml, P = 0.0001; P between groups = 0.619). Lean individuals had statistically significant higher increments of FAI and specifically FEI compared to overweight (FEI lean; 0.14±0.09 increased to 0.29±0.14, P = 0.009; overweight 0.23±0.18 increased to 0.52±0.40, P = 0.126; P between groups = 0.034). Although BMI does not affect total 17Β-estradiol changes, free sex steroid concentrations increase more steeply in lean compared to overweight women receiving oral low-dose HT. © 2011 The Obesity Society.